Parameter sensitivity of SWAP–PEARL models for pesticide leaching in macroporous soils - Urbina, C.A.F. (2020)
The outputs analyzed were the concentration in drainage water, the average concentration in groundwater between 1 and 2 m, and the concentration in the soil system at 100‐cm depth. Influential parameters found through the Morris method were analyzed using the Sobol–Jansen method. The results for bentazon indicate that the degradation half‐life (DT50), the bottom depth of the internal catchment (zic), and the proportion of the internal catchment at the soil surface (pic_0) are critical parameters in all the outputs analyzed. For imidacloprid and compound I, the most relevant parameters for drainage output are the Freundlich sorption exponent (Fexp) and zic; for groundwater, the relevant parameters are Fexp, the bottom depth of static macropores (zst), and pic_0; and for soil concentrations at 100‐cm depth, the relevant parameters are Fexp, zic, and pic_0. The Morris and Sobol–Jansen methods produce the same results for the first position in the ranking. Measurement efforts should be performed to update national soil databases, including critical pesticide and macropore parameters.